Immune and Apoptosis Mechanisms Regulating Placental Development and Vascularization in Preeclampsia - Raguema, Nozha; Moustadraf, Sarah; Bertagnolli, Mariane (Frontiers in Physiology, 2020)
Preeclampsia is the most severe type of hypertensive disorder of pregnancy, affecting one in 10 pregnancies worldwide and increasing significantly maternal and neonatal morbidity and mortality. Women developing preeclampsia display an array of symptoms encompassing uncontrolled hypertension and proteinuria, with neurological symptoms including seizures at the end of pregnancy. The main causes of preeclampsia are still unknown. However, abnormal placentation and placenta vascularization seem to be common features in preeclampsia, also leading to fetal growth restriction mainly due to reduced placental blood flow and chronic hypoxia. An over activation of maternal immunity cells against the trophoblasts, the main cells forming the placenta, has been recently shown as an important mechanism triggering trophoblast apoptosis and death. This response will further disrupt the remodeling of maternal uterine arteries, in a first stage, and the formation of new placental vessels in a later stage. A consequent chronic hypoxia stress will further contribute to increase placental stress and exacerbate systemic circulatory changes in the mother. The molecular mechanisms driving these processes of apoptosis and anti-angiogenesis are also not well understood. In this review, we group main evidences suggesting potential targets and molecules that should be better investigated in preeclampsia. This knowledge will contribute to improve therapies targeting a better placenta formation, having a positive impact on maternal disease prevention and on fetal development.